Intellectual Encounter Between Betawi and Banten Scholars: A Historical Perspective - Murodi; Muhtadi (GoAcademica Research & Publishing, 2024)
This study delves into the intricate connections between the ulama (scholars) of Betawi and Banten, primarily focusing on the dynamics of their relationships as teachers and students or amongst peers who shared the same mentors, particularly during their educational pursuits with the Sheikhs in Makkah. These relationships played a pivotal role in shaping the religious and intellectual landscape of the regions. The research adopts a qualitative approach, emphasizing the depth and complexity of these interpersonal and intellectual connections. Data collection was conducted through a combination of in-depth interviews and thorough documentation studies. Interviews were targeted at experts, historians, and local community leaders with deep insights into the lives and contributions of these scholars. Documentation studies involved an extensive review of historical records, writings of the ulama, and other relevant literature that shed light on the educational and spiritual journeys of these scholars. The findings of this research reveal a rich tapestry of interactions and exchanges among the ulama of Betawi and Banten. It was observed that they shared a close-knit relationship, often forming bonds that transcended the typical teacher-student dynamic, fostering a community of learning and spiritual development. This study underscores the significant role played by these scholars in establishing and advancing Islamic boarding schools and other educational institutions. These establishments not only served as centers for religious and academic learning but also acted as platforms for intellectual encounters and discussions. These interactions and institutions were instrumental in the dissemination of knowledge and the nurturing of future generations of scholars, thereby contributing significantly to the religious and educational landscape in Indonesia. This research provides a nuanced understanding of the socio-religious fabric of Betawi and Banten, highlighting the profound impact of these scholars in shaping the Islamic discourse and education in these regions.